Ewolucja zawartości prasy lokalnej w Polsce w latach dziewięćdziesiątych XX wieku - Kowalczyk, Ryszard (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2006)
The Author explains that the research into local press is mainly concerned with the departure from political, economic or manufacturing matters which are superseded by the problems of ordinary people. It is usually emphasized that the general outlook of local press is predominantly affected by three types of problems: social, cultural and sporting, with a particular stress on the historical aspect. The private commercial press is becoming dominated by issues concerning crime and scandals, sports and entertainment, and advertising and announcements as evidenced by an increasing proportion of these topics in the total volume of publications under consideration. However, in magazines which are produced by local governments the main topics concern the initiatives, importance and functions of local governments which makes these publications resemble popular notice bulletins.
The Evolution of Local Press Content in Poland in the 1990s